Accuracy of Ice Melting Capacity Tests: Review of Melting Data for Sodium Chloride. Issue 1 (2016) - Nilssen, Kine; Klein-Paste, Alex; Wåhlin, Johan
In cold climate regions, chemicals are often applied on roads to facilitate snow and ice removal. A commonly used performance indicator is the ice melting capacity. There is a growing need for stakeholders to measure melting capacity as more commercial products for deicing become available. There are two standardized test methods for measuring melting capacity, SHRP H-205.1 for solid deicers and SHRP H-205.2 for liquid deicers, but there have been concerns that these tests are not accurate. Researchers have developed alternative test methods, including the shaker test, the mechanical rocker test, and the ice cube titration test. This paper summarizes published data on measured melting capacity for sodium chloride (NaCl). The published data were compared with the calculated melting capacity of NaCl. The findings confirm that SHRP tests have low reproducibility and are not able to measure full melting capacity. The newer test methods measured closer to full melting capacity than the SHRP tests did. They also showed improved accuracy, although more data from the newer test methods are needed before conclusions can be drawn.